Beyond naming and shaming: New modalities of information politics in human rights. Issue 3 (2nd July 2016) - Pruce, Joel R.; Budabin, Alexandra Cosima
ABSTRACT: How and why does information become currency in human rights advocacy? Human rights organizations (HROs) produce media content in an increasingly diverse manner today across multiple platforms, for divergent purposes, and for distinct audiences. Advocacy practices are no longer confined to fact-based reporting aimed at exposing abuse. The sheer magnitude of resources expended in communication evidences the early stages of a shift in which HROs widen their broadcast and target mass audiences. However, human rights scholarship has not adequately addressed this new trend, which has the capacity to radically alter the advocacy landscape. Moving beyond the traditionally narrow focus on "naming and shaming, " we contend that a critical, detailed approach to understanding the strategic use of information will reveal a more complete image of how HROs build influence through their communications strategies. Expanding upon Keck and Sikkink's concept of "information politics, " we develop a theoretical framework that distinguishes a set of practices we call media advocacy . Three unique modalities of media advocacy (juridical, revelatory, and activating) capture a robust portrait of information politics in twenty-first century human rights advocacy. Our innovative tools disclose specific operational and pragmatic implications for HROs, as well as help structure future research in this area.